The influence of human and financial capital on the performance of woman entrepreneurs in micro and small enterprises in state of Perak, Malaysia - Md Saad, Amrina; Ali, Mass Hareeza; Guza, Garba Mohammed (Premier Publishers, 2018)
Woman entrepreneurs have a vital role in a country’s economic growth and development. This paper examined the impact of human capital and financial capital on the performance of woman entrepreneurs in Micro and Small Enterprises (MSEs). The paper employed quantitative method with usable questionnaires among women entrepreneurs. Pearson Correlation and Multiple Regression model were used to analyze data by using SPSS software and the results indicate that human capital has an impact on the business performance and the relationship is significant. On the other hand, financial capital has a significant impact on the profitability among women entrepreneurs with significant positive value.